PENGARUH BEBERAPA VARIABEL KINERJA KEUANGAN PERUSAHAAN FOOD AND BEVERAGES TERHADAP HARGA PASAR SAHAM DI BURSA EFEK INDONESIA - -, Alfiana (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
This study aimed to determine the effect of several variables of financial performance of the companys Food and Beverages stock market prices in Indonesia Stock Exchange . The independent variable in this study consisted of ROI , ROE , NPM , EPS and PER . This study also aimed to prove whether hadROI variables , ROE , NPM , EPS and PER affect the market price of the stock . In addition , this study also wants to know which variables that have a dominant influence on the market price of the stock .The sampling technique using purposive sampling technique . The data used is a combination of time series and cross section data ( pooled data) . The number of samples used in this study were 14 Food and Beverages companies that went public in the Indonesia Stock Exchange . The data analysis technique used in this study is multiple regression analysis ( Multipple Regression Analysis ) using SPSS software for windows 14 .Hypothesis test used in this research is the F test and t test . The results showed that the variables of ROI , ROE , NPM , EPS and PER together ( simultaneously ) have a significant effect on the magnitude of the market price of the stock in the companys financial performance assessment of food and beverages that go public in Indonesia Stock Exchange . This is evidenced by the F count of 50.044 . This value is greater than the F table (1.768 < 50.044 ) .EPS variable ( X4 ) has a dominant influence on stock market prices ( Y ) . It was shown the value of the standardized beta coefficients of 0.882 or 88.2 % to record another independent variable constant . EPS is an indicator of the success of the company management and describes the companys success in generating profits for shareholders . Based on the results of the calculation, the coefficient of multiple determination ( R Square) of 0.796 or 79.6 % , meaning that the independent variables included in this study has a contribution of 79.6 % to the market price of the stock . While 20.4 % influenced by other independent variables were not included in the research model . In this study also showed R = 0.892 ROI means the relationship between the variables ( X1 ) , ROE ( X2 ) , NPM ( X3 ) , EPS ( X4 ) and PER ( X5 ) to the market price of the stock ( Y ) is a very strong and positive . This means that if the variable ROI , ROE , NPM , EPS and PER increases, the variable stock market prices also increased and vice versa . Keywords : Return on Investment (ROI ) , Return on Equity (ROE ) , Net Profit Margin (NPM ), Earning Per Share (EPS), Price Earning Ratio (PER), the Market Price of Share